THE THERMAL SAFETY OF HIGH POWERED CLASS IV LASER ON FEMALE LATERO-POSTERIOR THIGHS: ANALYSIS WITH INFRA-RED THERMOGRAPHY (CIPEEX, 2025)
Introduction: Photobiomodulation using Class 3B lasers has been used to treat esthetic and muscle-skeletal conditions for decades. Recently, High Powered Lasers (Class IV) have also been introduced to treat esthetic problems, it has raised reasonable criticism regarding safety and possible increases in skin temperature. The aim of the present study was to evaluate possible skin temperature changes after irradiatiation using Infra-red thermography. Methods: Twenty-five female and four male participants were enrolled in the study. After, skin temperature profiles of both side of the flanks were recorded using infra-red thermography before and 1,5 and 10 min after photobioodulation with a High Powered Class IV Laser with total energy of 1464 Joules (14.6 J/Cm2). Results: No significant changes in skin temperature were produced after laser irradiation with both probes in both groups of female and male participants. Conclusions: We conclude that Class IV Laser when applied in scanning mode to the male and female hip regions did not induce any temperature changes immediately after irradiation or after 1, 5 or 10 minutes. In the energy doses used in this protocol, the high-powered Class IV Laser was considered completely safe to use for treatment.
Keywords: Phtobiomodulation; class IV laser; thermography; laser therapy